Li, Jun (comp.). 100 Glimpses into China; Short Short Stories from China. Peking: Foreign Language Press, 1989, 395 pp. Jeannette Faurot (comp.). Glimpses of China; Short Fiction for Chinese Study. San Francisco: China Books and Periodicals Inc., 1991, vi + 137 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1993)
-